Domestic Violence Againts Women Portrayed in Khaled Hosseini’s a Thousand Splendid Suns - Firyal Farah Fadhilah; Tuty Handayani (Insaniyat: Journal of Islam and Humanities, 2022)
Gender inequality and violence against women are critically discussed by scholars around the world. Set in Afghanistan, a country that still adheres to a patriarchal culture, Khaled Hosseini, in his novel A Thousand Splendid Suns, depicts how the two main female characters, Meriam and Laila, have to face domestic violence in their polygamous marriage with Rasheed. This research aims to show how domestic violence is portrayed in the novel A Thousand Splendid Suns by Khaled Hosseini and how the novel challenges domestic violence through the two main female characters, Mariam and Laila. The research used a qualitative method by utilizing the gender studies approach. Specifically, it used gender-based violence and domestic violence concept by Ganley. The result of the research shows that the two main female characters had to face three forms of domestic violence such as physical violence, psychological violence, and sexual violence; and the two female characters fight against Rasheed’s behavior and they finally get different freedoms, both physically and psychologically. In conclusion, the two female characters in the novel tried to challenge the practice of domestic violence instead of silently confronting it like women are expected to do.